2013
DOI: 10.1371/journal.pone.0059115
|View full text |Cite
|
Sign up to set email alerts
|

Cotton GalT1 Encoding a Putative Glycosyltransferase Is Involved in Regulation of Cell Wall Pectin Biosynthesis during Plant Development

Abstract: Arabinogalactan proteins (AGPs), are a group of highly glycosylated proteins that are found throughout the plant kingdom. To date, glycosyltransferases that glycosylate AGP backbone have remained largely unknown. In this study, a gene (GhGalT1) encoding a putative β-1,3-galactosyltransferase (GalT) was identified in cotton. GhGalT1, belonging to CAZy GT31 family, is the type II membrane protein that contains an N-terminal transmembrane domain and a C-terminal galactosyltransferase functional domain. A subcellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Then, the constructed GhRAV1:eGFP fusion gene was cloned into pBI121 vector, replacing the GUS gene. Tobacco leaf epidermal cells were injected with the GhRAV1:eGFP construct by Agrobacterium -mediated DNA transfer as described previously [ 20 ]. The cells transient-expressing GhRAV1 : eGFP gene under the control of CaMV 35S promoter were selected for detecting GFP fluorescence on a SP5 Meta confocal laser microscope (Leica, Germany) with a filter set of 488 nm for excitation and 506–538 nm for emission, after the injected tobacco leaves were cultured on MS medium for 72 h. SP5 software (Leica, Germany) was employed to record and process the digital images taken [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the constructed GhRAV1:eGFP fusion gene was cloned into pBI121 vector, replacing the GUS gene. Tobacco leaf epidermal cells were injected with the GhRAV1:eGFP construct by Agrobacterium -mediated DNA transfer as described previously [ 20 ]. The cells transient-expressing GhRAV1 : eGFP gene under the control of CaMV 35S promoter were selected for detecting GFP fluorescence on a SP5 Meta confocal laser microscope (Leica, Germany) with a filter set of 488 nm for excitation and 506–538 nm for emission, after the injected tobacco leaves were cultured on MS medium for 72 h. SP5 software (Leica, Germany) was employed to record and process the digital images taken [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Chlorophyll content was determined on a fresh-weight basis. Total chlorophyll from 0.1 g leaves of ten-day-old seedlings with or without NaCl treatment was extracted with 95% ethanol, and chlorophyll concentrations were calculated by the method described earlier [ 20 ] using spectrophotometer (TU-1901) and microplate reader (Bioteck, USA). Differences in chlorophyll content between wild type and the transgenic seedlings were evaluated using a P value generated by a one-sided t-test.…”
Section: Methodsmentioning
confidence: 99%
“…We designed gene‐specific primers for each gene and qRT‐PCR analyses do show that the expression levels of CotAD_70785, CotAD_68102, CotAD_43585 and CotAD_16822 were significantly reduced in GhGalT1 ‐silenced lines (Figure S10b). These data illustrate that the above five genes might function redundantly (or partially redundantly) to encode similar enzyme activity, and that cross‐silencing them led to the most prominent fiber phenotype; however, when heterologously expressed in Arabidopsis, GhGalT1 can promote plant growth (Qin et al ., ). These seemingly contrasting phenotypes may result from off‐target effects of the ectopic expression of GhGalT1 , or because the putative functional enzymatic complex formed in Arabidopsis may not be optimal because key interacting partners to a specific cell type (such as fiber cell) may be absent in Arabidopsis.…”
Section: Discussionmentioning
confidence: 97%
“…To date, no cotton glycosyltransferase linked to the biosynthesis of the AGP glycan moiety has been characterized in vivo . We previously identified a gene ( GhGalT1 ) encoding a putative galactosyltransferase (GalT) in cotton and found that the heterologous expression of GhGalT1 in Arabidopsis affected plant growth and development (Qin et al ., ). Here, we provide genetic, cellular and biochemical evidence that GhGalT1 is a galactosyltransferase involved in AGP β‐1,3‐galactan backbone biosynthesis, and proffer a mechanism by which AGPs participate in controlling the fiber development of cotton.…”
Section: Introductionmentioning
confidence: 97%
“…Extraction of cell wall residues (i.e., alcohol-insoluble residues [AIRs]) was conducted as described previously Qin et al, 2013). Cell wall crystalline cellulose amount was measured according to Kim et al (Kim et al, 2013).…”
Section: Cell Wall Extraction and Crystalline Cellulose Analysismentioning
confidence: 99%